2018
DOI: 10.1007/s11056-018-9654-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of soil preparation method on root development of P. sylvestris and P. abies saplings in commercial forest stands

Abstract: Soil preparation is a common practice that precedes outplanting of Norway spruce (Picea abies) and Scots Pine (Pinus sylvestris) in boreal forests. It has been proven to enhance the survival and early growth of seedlings. Containerized P. abies and P. sylvestris saplings were excavated 1-3 years after outplanting in clear cut forests across Latvia. The excavated saplings were grown in forests that had been prepared either using site mounding or disc trenching soil preparation method. The aim was to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The results of the preliminary study (data not shown) indicated that the mounding application could increase the distribution of the total roots up to 14 times. It was in line with a previous study that stated application of mounding on saplings of Norway spruce (Picea abies) and Scots Pine (Pinus sylvestris) produced a deeper root system (Celma et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the preliminary study (data not shown) indicated that the mounding application could increase the distribution of the total roots up to 14 times. It was in line with a previous study that stated application of mounding on saplings of Norway spruce (Picea abies) and Scots Pine (Pinus sylvestris) produced a deeper root system (Celma et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The newly made pit (Figure 1C) that formed to create the mounding in the interrow can accommodate excess water in the rainy season and maintain soil moisture during the dry season. It was following the previous study by Celma et al (2019). As a result, the pits increased the soil water content (Bohluli et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…Our fundamental questions were: (1) do different site preparation methods and microtopography alter species cover and richness; (2) do site preparation methods and microtopography interact to affect the abundance of forest and grassland habitat species; (3) do patterns of vegetation development differ depending on the soil type. We hypothesise that vegetation composition within the same soil type will be affected by the type of site preparation method because the trench created during disc trenching and the pit created during spot mounding are of different depths, thus having different effects on soil moisture and microtopograpic microclimate (Celma et al, 2019). We also hypothesise that microclimate in pit and trench will have a positive impact on some typical old forest species that could not be found on unprepared soil.…”
Section: Introductionmentioning
confidence: 99%
“…In Latvia, the most widespread site preparation method is disc trenching, in which the humus layer is removed and pushed to one side, creating a berm which provides a suitable microenvironment for planted tree growth (Lundmark-Thelin & Johansson, 1997;Luoranen & Rikala, 2013). Other applied methods include spot mounding, which is done by excavating soil and turning it over next to the newly made pit, thereby creating a place where mineral soil is exposed and the tree seedling can be planted (Celma et al, 2019). Spot mounding is more appropriate in areas with heavy precipitation and high water table, because newly made pits collect excess water and prevent tree seedlings from being drowned in high water table conditions, as well as provide water reserves for the drier periods (Gemmel et al, 1996;Heiskanen et al, n.d.;Nieminen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Soil temperature and water availability are among the main factors determining the distribution pattern and growth of the roots, and it is one of the most important conditions for plant growth and survival (Grossnickle, 2005). Also soil preparation method has impact on root system development and orientation (Celma et al, 2019). For example, in a harsh environment, as in the north of Scandinavia, soil temperature is one of the main abiotic factors determining the growth of trees (Nilsson et al, 2010) These factors can be affected differently by chosen soil preparation method.…”
Section: Introductionmentioning
confidence: 99%